„Anamnese“ eines Nicht-Täters Ukrainer und der Holocaust in Leonid Gorovec’ Der Damenschneider - Kobrynskyy, Oleksandr (Glücksuchende? : Conditio Judaica im sowjetischen Film, 2011)
Keywords: Holocaust; Film

Auschwitz and Afterimages - Kobrynskyy, Oleksandr (Holocaust Studies, 2013)

DEFA's Forgotten Memory: The Holocaust in East German Film - Kobrynskyy, Oleksandr (The London Film and Media Reader 1, 2013)
Keywords: Holocaust; Film; DDR; DEFA; Erinnerung; Drittes Reich

Defining the Jew: The Origins of the Nuremberg Laws - Kobrynskyy, Oleksandr (Nazi Law: From Nuremberg to Nuremberg, 2017)
Keywords: Drittes Reich; Nationalsozialismus; Nürnberg; Nürnberger Gesetze; Holocaust; Justiz; Judentum

Holocaust Cinema in the Twenty-First Century: Images, Memory, and the Ethics of Representation - Bayer, Gerd; Kobrynskyy, Oleksandr (Wallflower-Columbia University Press, 2015)

Holocaust Literature: A History and Guide - Kobrynskyy, Oleksandr (Holocaust Studies, 2014)

Introduction: The Next Chapter in the History of Holocaust Cinema - Bayer, Gerd; Kobrynskyy, Oleksandr (Holocaust Cinema in the Twenty-First Century: Images, Memory, and the Ethics of Representation, 2015)

Memorial Njurnbergskie Processy. Vystavka. - Kobrynskyy, Oleksandr (2016)
Übersetzung des Ausstellungskatalogs Memorium Nürnberger Prozesse. Die Ausstellung (Museen der Stadt Nürnberg) ins Russische.
Keywords: Nürnberg; Nürnberger Prozesse; Katalog; Ausstellung

The Bloomsbury companion to Holocaust literature - Kobrynskyy, Oleksandr (Holocaust Studies, 2015)
Keywords: Holocaust; Literatur

The Holocaust as Case Study: Universalist Rhetoric and National Memory in Stefan Ruzowitzky's Radical Evil - Kobrynskyy, Oleksandr (Holocaust Cinema in the Twenty-First Century: Images, Memory, and the Ethics of Representation, 2015)